Ion exchanger BIONA 312 as a component of soils polluted with nickel in cultivation of cucumber (Cucumis sativus L.) - Renata Matraszek (Acta Agrobotanica, 2013)
The objective of the studies undertaken was to assess the possibility of ion exchange substrate BIONA 312 use for nickel bioavailability limitation in cucumber (Cucumis sativus L.) 'Hermes'cv. as determined on the ground of chlorophyll and Ni content. BIONA 312, regarding the chemical composition, is a mixture of strongly acid cation exchanger KU-2x8 and polyfunctional weakly alkaline anion exchanger EDE-10P. The experiment was differentiated in regard to nickel and ion exchanger content. The following doses of Ni (in the form of NiSO4) were introduced: 0,30 or 75mg Ni·dm-3 of the substrate. BIONA 312 was added to the medium in the following doses: O,2 or 5% of substrate volume. Together with Ni dose increase in the medium there was recorded a significant increase of this metal concentration in the cucumber biomass. Nickel in the amount 30 mg dm-3 did not affect considerably the changes in any of chlorophyll form, but a dose 75mg Ni·dm-3 has caused a significant decrease in chlorophyll "a" concentration in cucumber leaves. Simultaneously with the increase in the nickel content in the nutritive environment the decrease in the value of organic mass productivity coefficient was observed. The introduction of 5% ion exchange substrate BIONA 312 into the medium containing nickel in the amount 30 or 75 mg·dm-3 induced a significant growth of the studied chlorophyll fractions in the cucumber leaves. BIONA 312 introduced to the environment contaminated with nickel in the amount of 30 or 75 mg·dm-3 has significantly reduced Ni content in the cucumber biomass simultaneously increasing participation of roots in organic mass production. More efficient for the reduction of harmful Ni effect on the cucumber plants turned out to be introduction of ionite sorbent BIONA 312 at the dosage 5% than 2%.